Microeconomics: a contemporary approach - Cole, Charles L. (New York, Harcourt Brace Jovanovich, 1973)
"Real-world problems and issues in the text and in featured Applications provide abundant concrete, living examples to show microeconomic theory in action. The text goes beyond basic theory to explain theories and applications from important contemporary fields of economics, including industrial organization, labor economics, international trade, public finance, transaction costs, adverse selection, limited.
Including bibliographical references.and index
aia 06/09/18
Loan
Keywords: Microeconomics; Microeconomics